Humour and other catastrophes: dealing with the translation of mixed-genre TV Series - Bucaria, Chiara (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Starting from a trend observed in the Italian dubbing of US series “Six Feet Under” (Bucaria 2005; Bucaria forthcoming) involving the deletion or toning down of most instances of potentially disturbing elements, this paper will take into consideration examples from three US TV series (“House MD,” “Nip/Tuck” and “Six Feet Under”) dubbed into Italian and presenting a mixture of drama and comedy, in an attempt to analyze the degree of manipulation or adaptation that they underwent in terms of the linguistic representation of clashing genres. With particular reference to the rendering of humorous comments produced in unexpected contexts, the analysis shows considerable manipulation in the translated versions and a consequent decrease in the humorous content of the target texts.